An innovative Mg/Ti hybrid fixation system developed for fracture fixation and healing enhancement at load-bearing skeletal site. (October 2018) - Tian, Li; Sheng, Yifeng; Huang, Le; Chow, Dick Ho-Kiu; Chau, Wing Ho; Tang, Ning; Ngai, To; Wu, Chi; Lu, Jian; Qin, Ling
Abstract: Magnesium (Mg) is a potential biomaterial suitable for developing biodegradable orthopaedic implants, especially as internal fixators for fracture fixation at non-load bearing skeletal sites. However, Mg alone cannot provide sufficient mechanical support for stable fracture fixation at load bearing sites due to its rapid degradation in the early stage after implantation. In consideration of the strengths and weaknesses of Mg, we developed an innovative magnesium/titanium (Mg/Ti) hybrid fixation system for long bone fracture fixation and investigated the fixation efficacy. The finite element analysis (FEA) results indicated that the Mg/Ti hybrid fixation system provided sufficient mechanical support for fracture fixation at load-bearing skeletal site. As a proof-of-concept, we performed a "Z-shaped" open osteotomy at the mid-shaft of rabbit tibia. For comparison, the animals were divided into two groups: Mg/Ti group (fixated with Mg screws and Ti fixators) and Ti control group (fixated with Ti screws and Ti fixators). The radiographic, four-point bending mechanical test, histological and histomorphometric analysis were postoperatively performed in a temporal manner up to 12 weeks. Both X-ray and micro-CT images of the Mg/Ti group showed a larger callus (14.7% at 3rd week and 24.8% at 6th week, n = 5–7, p < 0.05) in the regions of interest (ROIs) over time, especially at the opposite cortex of the fixation plate. At the 12th week post-operation, the biomechanical test result indicated that the rabbit tibia in the Mg/Ti group healed better and the overall mechanical strength was approximately 3-fold higher (n = 8, p < 0.05) than that at 6th week. Furthermore, the FEA revealed that the Mg/Ti group had a higher mechanical strength (19.5% at week 6 and 31.5% at week 12) at the specified ROI and resulted in an earlier and faster endochondral ossification (68.0% at week 3 and 71.4% at week 6) with a higher expression of osteocalcin (54.0%) and collagen I (34.2%) than the Ti control group (n = 4, p < 0.05). Further evaluation suggested that a higher expression of calcitonin gene-related peptide (CGRP), a known osteogenic neuron peptide, in the fracture callus of the Mg/Ti group might be a major underlying mechanism of enhanced fracture healing attributed to the release of Mg ions during the degradation of Mg screws.